The Effects of Illegal Small-scale Gold Mining in Ghana: A Threat to Food Security - Gilbert, Danyo (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
Ghana is endowed with extensive mineral and agricultural resources. Those mined on commercial basis include gold, bauxite, diamond and manganese. Others such as kaolin, salt, limestone, mica, feldspar, to mention a few are either only partially exploited or unexploited. The regions which serve as the major agro-ecological zones coincide with the largest deposits of mineral resources. Destruction of arable land in the agro-ecological zones by illegal small-scale gold mining (galamsey) affects agricultural productivity, and threatens food security in Ghana. This article examines the impact of the effects of illegal small-scale gold mining in Ghana, through the lens of a conceptual model that links galamsey and agricultural productivity, in terms of the realistic threat to food security, using secondary data such as Ghana’s agricultural productivity records, consumer price indices of food commodities, and the national food import statistics. The data show that, major galamsey regions (Ashanti, Brong Ahafo, Eastern, Central and Western), recorded progressively lower food productivity and correspondingly higher Consumer Price Indices than the national averages over the last few years (from 2012). Over the same period, the contribution of agriculture to the gross domestic product (GDP) declined inversely with mining. By degrading arable lands, contaminating water bodies, polluting the air, shifting labour from food crop farming to mining and displacing farmers, galamsey by surface mining is largely responsible for the low food production, food price spikes and the high cost of living, especially in galamsey-prone regions of Ghana. But surface mining can be a short term land use that may be followed by productive farmland, if reclamation is done correctly. Land expansion from reclamation of degraded open cast mines will boost agricultural productivity; close existing yield gaps in crops, enabling the country to achieve food import substitution for major food staples, particularly cereals such rice and wheat. This in turn, will reduce the national import food dependence, food import bill, food price hikes and the cost of living. Thus, reclamation of degraded galamsey-mines is critically important in achieving all three dimensions of the United Nation’s Sustainable Development Goals (social, economic and environmental), and more specifically goal two (end hunger, achieve food security, improved nutrition and promote sustainable agriculture) of the Post-2015 Agenda. The author therefore, recommends compulsory reclamation of degraded surface mines for arable use, as a sustainable proposition to mitigate the threat of food insecurity in Ghana. The threat to food security is real and imminent!